KAJIAN DIGITAL ETHOS PIMPINAN MADRASAH DAN DAMPAKNYA PADA MUTU LAYANAN ADMINISTRASI PENDIDIKAN ISLAM - Tri Reza Wibowo; Siti Aimah (STKIP Pesisir Selatan, 2026)
This study aims to analyze the role of school leaders’ digital ethos and its impact on the quality of Islamic education administrative services in the context of digital transformation. The research was conducted at MTs Al-Amiriyah as a representative case of a madrasa developing digital-based administrative services amid limited technological infrastructure. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participatory observations, and document studies involving the head of the madrasa, administrative staff, teachers, and service users. The data were thematically analyzed using triangulation techniques to ensure the validity of the findings. The results indicate that the digital ethos of school leaders is a more decisive factor in improving the quality of administrative services than the mere availability of technological infrastructure. Leaders with a strong digital ethos are able to transform work culture, optimize the use of limited technology, and shift the role of administrative staff from procedural tasks to user-oriented services. Furthermore, the integration of digital ethos with Islamic leadership values such as trustworthiness (amanah), honesty, justice, deliberation (musyawarah), and sincerity produces a value-based digital transformation model that strengthens ethics, accountability, and user satisfaction.